Strategies to prevent HIV transmission among heterosexual African-American women - Peters Ronald J; Meshack Angela F; Essien E James; Ogungbade GO; Osemene Nora I (BMC, 2005)
Abstract Background African-American women are disproportionately affected by HIV, accounting for 60% of all cases among women in the United States. Although their race is not a precursor for HIV, the socioeconomic and cultural disparities associated with being African American may increase their risk of infection. Prior research has shown that interventions designed to reduce HIV infection among African-American women must address the life demands and social problems they encounter. The present study used a qualitative exploratory design to elicit information about strategies to prevent HIV transmission among young, low-income African-American women. Methods Twenty five low income African American women, ages 18-29, participated in five focus groups of five women each conducted at a housing project in Houston, Texas, a large demographically diverse metropolitan area that is regarded as one of the HIV/AIDS epicenters in the United States. Each group was audiotaped, transcribed, and analyzed using theme and domain analysis. Results The participants revealed that they had most frequently placed themselves at risk for HIV infection through drugs and drinking and they also reported drug and alcohol use as important barriers to practicing safer sex. The women also reported that the need for money and having sex for money to buy food or drugs had placed them at risk for HIV transmission. About one-third of the participants stated that a barrier to their practicing safe sex was their belief that there was no risk based on their being in a monogamous relationship and feeling no need to use protection, but later learning that their mate was unfaithful. Other reasons given were lack of concern, being unprepared, partner's refusal to use a condom, and lack of money to buy condoms. Finally, the women stated that they were motivated to practice safe sex because of fear of contracting sexually transmitted diseases and HIV, desire not to become pregnant, and personal experience with someone who had contracted HIV. Conclusion This study offers a foundation for further research that may be used to create culturally relevant HIV prevention programs for African-American women.